Association Between Depressive Symptoms and Comorbidities Among Elderly Diabetic Individuals in China - Luyao Qiao; Xin Pan; Tianpei Li; Shouqin Yi; Zhenyu Tang (Brain and Behavior)
ABSTRACT Background Diabetic individuals are at an increased risk of mental illness and comorbidities. However, the precise association between depressive symptoms and comorbidity remains uncertain. Our study aimed to investigate this relationship among elderly Chinese diabetic patients. Methods Data from the China Health and Retirement Longitudinal Study (CHARLS) in 2020 were utilized for the cross‐sectional analysis. Depressive status was defined as the dependent variable, while the presence, number, and type of comorbidities served as independent variables. Logistic regression analyses were performed, adjusting for potential demographic factors, and health status and functioning factors. Results Our findings indicate that diabetic patients with complications are more likely to experience depression. With the exception for dyslipidemia (OR = 1.195, 95% CI: 0.969, 1.475), individuals with hypertension, heart disease, stroke, kidney disease, memory‐related disease, or arthritis/rheumatism were prone to develop depressive status in the fully adjusted model. After adjusting for covariates, diabetic patients with memory‐related diseases exhibited the most pronounced association with depressive symptoms (OR = 2.673, 95% CI: 1.882, 3.797). Furthermore, an increasing number of depression‐related comorbidities strengthened the association (p < 0.05). Sensitivity analysis revealed that there were no significant differences stratified by gender or marital status (p < 0.05). Conclusions In the elderly diabetic population in China, the presence, number, and type of comorbidities were independently associated with depressive symptoms. Diabetic patients with memory‐related diseases displayed the highest likelihood of experiencing depressive status. These findings underscore the importance of implementing effective strategies for multimorbidity management in diabetic patients.